2019
DOI: 10.18502/ijph.v48i1.787
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Endurance, Anxiety, and Coping Style among Journalists Engaged in Emergency Events: Evidence from China

Abstract: Background: During reports of emergency events, journalists experience psychological crisis and negative emotions aroused by the events. The psychological endurance of journalists, which is induced by high risks of the career, has attracted widespread attention. Emotional state and coping style are important factors that influence the psychological endurance of individuals. This study aimed to analyze the relationship of psychological endurance with anxiety and coping style among journalists engaged in emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…The results of this study are consistent with the findings of previous studies (9,19,20,21,22,23,24). Effective problem-focused coping strategies are often associated with reduced psychological stress, and by increasing the confidence of a woman's breast cancer, her problem-solving skills improve and lead to greater marital satisfaction.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study are consistent with the findings of previous studies (9,19,20,21,22,23,24). Effective problem-focused coping strategies are often associated with reduced psychological stress, and by increasing the confidence of a woman's breast cancer, her problem-solving skills improve and lead to greater marital satisfaction.…”
Section: Discussionsupporting
confidence: 91%
“…We identified that the avoidant coping style was associated with poor mental health, which is consistent with the results of Dawson et al 50 and Gurvich et al 51 , who suggest that avoidance coping behaviors (such as fantasy, avoidance, self-blame, and laissez-faire) negatively affect psychological well-being. Previous studies on psychological crises or emergency events reported that avoidant coping is correlated with lower psychological endurance, 52 less perceived control, 53 and higher levels of anxiety-like behavior. 54 However, unlike those of previous studies, 53 , 55 our findings showed that there was little correlation between an active coping style and participants’ public emergency psychological state.…”
Section: Discussionmentioning
confidence: 90%
“…The previous study related to traumatic stress events has reported that those in the general population with traumatic stress experiences were more likely to adopt a negative coping style [9]. Many previous studies have shown that different coping styles, especially negative coping styles, for trauma stress events are also related to subsequent mental illness [7,10,32]. In contrast, a positive coping style may promote emotional well-being [33].…”
Section: Plos Onementioning
confidence: 99%
“…At the same time, as the epidemic continues, general population gradually experience different levels of psychological distress, such as nervousness, fear of infection, anxiety, depression, sleep problems, and inattention [3,4]. Previous studies have reported that some psychological problems often occur during similar epidemic [5,6] or other traumatic stress events, such as natural disasters [7,8], disease [9], or long-term employment in high stress occupations [10][11][12], and may last for a long time [13,14].…”
Section: Introductionmentioning
confidence: 99%